2019
DOI: 10.3390/ijerph16122104
|View full text |Cite
|
Sign up to set email alerts
|

Non-Motor Symptoms after One Week of High Cadence Cycling in Parkinson’s Disease

Abstract: The objective was to investigate if high cadence cycling altered non-motor cognition and depression symptoms in individuals with Parkinson’s disease (PD) and whether exercise responses were influenced by brain-derived neurotrophic factor (BDNF) Val66Met polymorphism. Individuals with idiopathic PD who were ≥50 years old and free of surgical procedures for PD were recruited. Participants were assigned to either a cycling (n = 20) or control (n = 15) group. The cycling group completed three sessions of high cade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 54 publications
(68 reference statements)
1
12
0
Order By: Relevance
“…One study (157) reported that a sedentary program may be more beneficial to boys' moods than exercise. Another study (158) reported that 1-week high cadence cycling failed to improve depression symptoms. Methodological weaknesses, excessively severe depressive symptoms in participants, discrepancies in the mean age of the sample, imperfect exercise programs, and bias would affect the results.…”
Section: The Therapeutic Effect Of Exercise On Depressionmentioning
confidence: 99%
“…One study (157) reported that a sedentary program may be more beneficial to boys' moods than exercise. Another study (158) reported that 1-week high cadence cycling failed to improve depression symptoms. Methodological weaknesses, excessively severe depressive symptoms in participants, discrepancies in the mean age of the sample, imperfect exercise programs, and bias would affect the results.…”
Section: The Therapeutic Effect Of Exercise On Depressionmentioning
confidence: 99%
“…Multiple small controlled trials have demonstrated that forced high cadence cycling (FHCC) can ameliorate motor symptoms in individuals with PD as measured by the Unified Parkinson's Disease Rating Scale‐Part III and Timed up and Go (Alberts et al., 2011; Beall et al., 2013; Harper et al., 2019; McGough et al., 2016; Miller Koop et al., 2019; Ridgel et al., 2009, 2011, 2013, 2015; Uygur et al., 2015). In FHCC, individuals with PD pedal with either a tandem corider or a motor providing external augmentation at a cadence of 80–90 revolutions per minute (rpm)—which is faster than most individuals would pedal on their own.…”
Section: Introductionmentioning
confidence: 99%
“…Although the rate is augmented, cycling on either device is an active, not passive, activity. In comparing FHCC versus cycling at a self‐selected cadence on a stationary indoor bicycle, most of the published literature has found that, despite similar cardiovascular exertion in the two modes, improved motor symptoms are only observed in the forced‐cadence modality (Harper et al., 2019; Ridgel et al., 2009, 2015; Uygur et al., 2015). One recent study did demonstrate gains in both forced and voluntary groups, but it was noted that the voluntary group self‐selected to pedal at a cadence near the target achieved by the forced group (Miller Koop et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple small controlled trials have demonstrated that FHCC can ameliorate motor symptoms in individuals with PD as measured by the Uni ed Parkinson's Disease Rating Scale-Part III and Timed up and Go. [22][23][24][25][26][27][28][29][30][31] In FHCC, individuals with PD pedal with either a tandem co-rider or a motor providing external augmentation at a cadence of 80-90 revolutions per minute (rpm)-which is faster than most individuals would pedal on their own. Although the rate is augmented, cycling on either device is an active, not passive, activity.…”
Section: Introductionmentioning
confidence: 99%